The Role of Communication & HR Development Towards Improving Archives Governance Performance - Eric Hermawan; Widiastuti Furbani; Gilbert Nainggolan; Nining Latianingsih; Dipa Teruna Awaludin (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to examine the influence of communication and human resource development on improving archival governance. Research Methodology: A quantitative research design was applied using regression analyses. This study employed purposive sampling with a total of 97 respondents. Data were collected through questionnaires distributed to employees of the Central Java Provincial Education and Culture Office and analyzed using the SPSS software. Results: The results indicate that communication significantly affects governance governance performance. Human resource development also has a strong influence on performance. In addition, both communication and human resource development have a significant impact on the performance of archival governance. Conclusions: The SPSS results indicate that communication and human resource development significantly impact archival governance performance. Together, they explain 22.5% of the variation in performance, with the remaining 77.5% influenced by factors not covered in this study. Limitations: The findings highlight that effective communication and human Effective communication improves information delivery and participation, while human resource development enhances employee competence and professionalism, both crucial for enhancing archival governance performance and efficient archival management.                                 Contributions: Effective communication and competent Human Resource (HR) development are crucial for improving archive governance performance. Good communication ensures clear information regarding archive management, while HR development ensures the availability of skilled personnel to manage archives. Novelty: Effective communication and HR development are key to improving archival governance, ensuring efficient information delivery and professional and competent management of archival affairs.